2021
DOI: 10.1371/journal.pgen.1009366
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the septal peptidoglycan synthase FtsWI complex supports a conserved activation mechanism for SEDS-bPBP complexes

Abstract: SEDS family peptidoglycan (PG) glycosyltransferases, RodA and FtsW, require their cognate transpeptidases PBP2 and FtsI (class B penicillin binding proteins) to synthesize PG along the cell cylinder and at the septum, respectively. The activities of these SEDS-bPBPs complexes are tightly regulated to ensure proper cell elongation and division. In Escherichia coli FtsN switches FtsA and FtsQLB to the active forms that synergize to stimulate FtsWI, but the exact mechanism is not well understood. Previously, we i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 43 publications
2
45
0
Order By: Relevance
“…For FtsW to synthesize septal PG, it must bind its substrate lipid II and polymerize the disaccharide pentapeptide into glycan strands. In addition, previous studies showed that FtsW must bind FtsI as it is activated by a pathway that operates through its cognate bPBP (PBP3/FtsI) [30][31][32]. Thus, there are at least three possibilities for the observed defect in septal PG synthesis: inability to bind lipid II, a defect in catalysis or a defect in the activation step.…”
Section: Dominant-negative Ftsw Mutants Bind Ftsi and Lipid II In Vitromentioning
confidence: 99%
See 3 more Smart Citations
“…For FtsW to synthesize septal PG, it must bind its substrate lipid II and polymerize the disaccharide pentapeptide into glycan strands. In addition, previous studies showed that FtsW must bind FtsI as it is activated by a pathway that operates through its cognate bPBP (PBP3/FtsI) [30][31][32]. Thus, there are at least three possibilities for the observed defect in septal PG synthesis: inability to bind lipid II, a defect in catalysis or a defect in the activation step.…”
Section: Dominant-negative Ftsw Mutants Bind Ftsi and Lipid II In Vitromentioning
confidence: 99%
“…Accumulated evidence suggests that the activity of the SEDS-bPBP complexes in vivo is regulated by an activation pathway that goes through bPBP to stimulate the PG polymerase activity of its cognate SEDS protein [10,11,[30][31][32]. In the elongasome, the activity of RodA-PBP2 is believed to be regulated by MreC and MreD [11,33], two critical components of the elongasome.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In current models, activation begins with the midcell localization of FtsN ( 18 , 19 , 20 ) ( Fig. 1 C ), which communicates with FtsWI through a cytoplasmic route involving FtsA ( 21 , 22 , 23 ) and through a periplasmic route involving the FtsLB complex ( 21 , 24 , 25 , 26 , 27 ). In this work, we focus on the latter periplasmic activation route.…”
mentioning
confidence: 99%